FAKTOR SOSIAL DAN FAKTOR EKONOMI PADA USAHATANI MANGGA SERTA PENGARUHNYA TERHADAP PEMASARAN MANGGA (Studi Kasus Di Dua Daerah Sentra Produksi Mangga di Jawa Barat) - Elly Rasmikayati; Muhammad Nugroho Bayu Utomo Sumarsah; Dika Supyandi; Adi Nugraha; Bobby Rachmat Saefudin (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Marketing activities carried out by mango farmers can be influenced by various factors. These factors include social factors and economic factors. The purpose of this study was to identify social factors, economic factors and mango marketing subsystems in Cikedung and Japara sub-districts and to analyze the influence of social and economic factors on mango marketing in both areas. This study uses a survey method to 260 mango farmers in Cikedung and Japara sub-districts. The analytical tools used in this research are descriptive statistis analysis and multiple linear regression. The results showed that the variables of social and economic factors in the two sub-districts were in good condition. Meanwhile, in mango marketing, Cikedung sub-district is relatively better than Japara sub-district. Social factors have a significant effect on mango marketing in Cikedung sub-district, while the economic factors have no effect. In the district of Japara sub-district, social and economic factors have no effect on mango marketing.